The association of problematic usage of the internet with burnout, depression, insomnia, and quality of life among Hungarian high school students - Feher, Andrea; Fejes, Eva; Kapus, Krisztian; Jancsak, Csaba; Nagy, Gabor Daniel; Horvath, Lilla; Tibold, Antal; Feher, Gergely (Frontiers in Public Health, 2023)
Introduction The extensive availability of the internet has led to the recognition of problematic usage of the internet (PUI) or so called internet addiction (IA), probably mostly involving adolescents. Aim Here we present a study focusing on the incidence and consequences (including burnout, which is relatively rarely studied) of internet addiction among high school students using a questionnaire-based non-random sampling cross-sectional survey. Included questionnaires were the Problematic Internet Use Questionnaire, the Maslach Burnout Inventory General Survey for Students MBI-GS (S), the 9-item short version of Beck Depression Inventory (BDI-SF), the Athens Insomnia Questionnaire and the EQ-5D (quality of life) questionnaire. Data were evaluated the exertion of Student’s t-test, chi square test and Pearson’s rank-order correlation. Logistic regression analysis was used to determine the significance of the different parameters as independently associated with PUI. Results Overall 3,000 paper-based questionnaires were successfully delivered and 2,540 responses received (response rate of 84.6%). 1,309 males (mean age 17.6 ± 1.43 years) (51.5%) and 1,231 females (mean age 17.5 ± 1.4 years) (48.5%) took part in our study. Problematic usage of the internet was detected in 486 (19.1%) students (232 males, mean age 17.6 ± 1.35 years and 254 females, mean age 17.34 ± 1.37 years). In a logistic regression analysis sleep disturbance (OR: 1.84, 95% CI: 1.83–2.03), depression (OR: 1.97, 95% CI: 1.77–2.02) and burnout (OR: 1.8, 95% CI: 1.16–1.94) were significantly associated with PUI. Conclusion Nearly one fifth of our study population suffered from PUI, which was strongly associated with school burnout, insomnia and depression, which underlines the importance of this phenomenon.